IDENTIFIKASI SISA MATERIAL KONSTRUKSI PADA PROYEK PEMBANGUNAN PELABUHAN - Yusrizal, Muhamad; Setiawan, Budi (Jurusan Teknik Sipil, Fakultas Teknik, Universitas Borneo Tarakan, 2023)
ABSTRACT: Construction project activity is a long process, in its implementation many problems and obstacles are encountered. One of them is the problem of residual material which is a serious problem in the implementation of construction projects. Efforts to minimize waste of construction materials will help increase profits and reduce environmental impact. Based on these problems, it is necessary to conduct research on materials that have the potential to become residual materials. Data collection was obtained from the company administration to support the calculation. Data processing begins with classifying material types, identifying potentially waste material with pareto analysis, calculating waste volume, calculating waste level, ranking potentially waste material based on waste level, calculating waste cost, ranking potentially waste material based on waste cost, structured interviews with respondents . From the results of material analysis, the remaining construction materials for the Port Development Project (Case Study: Development of Tengkayu Port 1 Phase 5, Tarakan City), are 5 mm dark blue glass, galvanized 5